Implementation Of Extracurricular Dance Art In Stimulating Children's Gross Motor Skills In The Muslim Cadani Integrated Islamic Kindergarten In The 2024/2025 Academic Year - Kurnia, Ila; Hamdani, Muhammad; Alawiyah, Tuti (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstract. This study aims to analyze the effect of the application of obstacle course games in increasing children's learning motivation, as well as identifying factors that support its effectiveness. which was carried out at RA Teladan Imam Syafi'i Dusun karang langu, Jalan Lading-lading kec. Tanjung, North Lombok Regency. With the number of students is 23 children consisting of 4 boys and 19 girls. The impact of this study showed a significant increase in children's learning motivation, including enthusiasm, concentration, and willingness to complete tasks. The game also helped develop social skills. The research used a qualitative approach with a case study method through observations, interviews and questionnaires of 5-6 year old learners involved in the obstacle course game. Data were analyzed descriptively to measure changes in learning motivation before and after the intervention.The results showed that the obstacle course game is effective in increasing children's learning motivation because it combines physical, mental, and collaborative elements. The implication is that this method can be integrated into active learning approaches to create a more engaging and impactful educational experience.Keywords: Obstacle course, learning motivation, children's education